Cupric Oxide Nanoparticles Induce Cellular Toxicity in Liver and Intestine Cell Lines - Mahmoud Abudayyak; Elif Guzel; Gül Özhan (Tabriz University of Medical Sciences, 2020)
Purpose: The wide application of cupric oxide nanoparticles (copper (II) oxide, CuO-NPs) in various fields has increased exposure to the kind of active nanomaterials, which can cause negative effects on human and environment health. Although CuO-NPs were reported to be harmful to human, there is still a lack information related to their toxic potentials. In the present study, the toxic potentials of CuO-NPs were evaluated in the liver (HepG2 hepatocarcinoma) and intestine (Caco-2 colorectal adenocarcinoma) cells. Methods: After the characterization of particles, cellular uptake and morphological changes were determined. The potential of cytotoxic, genotoxic, oxidative and apoptotic damage was investigated with several in vitro assays. Results: The average size of the nanoparticles was 34.9 nm, about 2%-5% of the exposure dose was detected in the cells and mainly accumulated in different organelles, causing oxidative stress, cell damages, and death. The IC50 values were 10.90 and 10.04 µg/mL by MTT assay, and 12.19 and 12.06 µg/mL by neutral red uptake (NRU) assay, in HepG2 and Caco-2 cells respectively. Apoptosis assumes to the main cell death pathway; the apoptosis percentages were 52.9% in HepG2 and 45.5% in Caco-2 cells. Comet assay result shows that the highest exposure concentration (20 µg/mL) causes tail intensities about 9.6 and 41.8%, in HepG2 and Caco-2 cells, respectively. Conclusion: CuO-NPs were found to cause significant cytotoxicity, genotoxicity, and oxidative and apoptotic effects in both cell lines. Indeed, CuO-NPs could be dangerous to human health even if their toxic mechanisms should be elucidated with further studies.